Ralstonia solanacearum, a deadly pathogen: Revisiting the bacterial wilt biocontrol practices in tobacco and other Solanaceae - Ahmed, Waqar; Yang, Jun; Tan, Yujiao; Munir, Shahzad; Liu, Qi; Zhang, Jinhao; Ji, Guanghai; Zhao, Zhengxiong (Rhizosphere, 2022)
Bacterial wilt disease caused by Ralstonia solanacearum species complex poses a great threat to Solanaceae and flue-cured tobacco crop production worldwide. R. solanacearum invades plants through roots, colonizes the vascular system, and blocks xylem tissues. Typical unilateral wilting symptoms appear on above-ground plant parts that lead to plant death. Integrated disease management strategies in the form of cultural control, chemical control, and genetic resistance have been employed for years to control the incidence of bacterial wilt disease. However, none of these strategies has completely controlled the disease due to high genetic diversity, broad host range, and prolonged survival of pathogen in soil and on plant parts. Owing to co-management strategies, biological control is the best approach for human health and environmentally safety. Biocontrol agents (endophytes and rhizobacteria) are ubiquitous with all plant parts (leaves, stem, roots, and rhizosphere), play an important role in disease suppression and growth promotion. The possible biocontrol mechanisms involve multifaceted interactions between host, pathogen, and antagonists is niche exclusion, nutrient acquisition, direct antagonistic, induction of resistance, and production of antimicrobial compounds. Studies have shown that biocontrol agents efficiently reduce the incidence of bacterial wilt disease in greenhouse experiments, but the field trials have not produced fruitful results. In this review, we made an effort to summarize the information related to microbe-assisted biocontrol of plant pathogens with main focus on bacterial wilt disease of flue-cured tobacco and Solanaceous crops.